Social Perspective : The Missing Element in Mental Health Practice - U'Ren, Richard C. (Book collections on Project MUSE., 2011)
"Social Perspective explores the impact of social factors on individual health, a topic often overlooked in the practice of psychiatry, psychology, and medicine. Richard U'Ren synthesizes viewpoints and information usually dispersed among many disciplines to show how social roles, political-economic conditions, and the social stratification system all contribute to individual well-being or disorder. U'Ren investigates how access to income, education, and social affiliations buffers individuals against stress and facilitates coping. He demonstrates that those who lack access to such resources suffer the poorest health and the greatest mental distress - a problem that has only grown more challenging with rising inequality. Adding a new dimension to understandings of mental health, mental illness, and psychological distress, Social Perspective offers clinicians a concise account of society's impact on the individual."--Pub. desc.